2020
DOI: 10.21037/tcr-20-2836
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the expression of plasma omentin-1 level in colorectal cancer and its correlation with prognosis

Abstract: Background: Colorectal cancer (CRC) is a malignant tumor of the digestive tract, with high incidence and mortality. This study aims to investigate the expression of plasma omentin-1 level in patients with CRC and its correlation with the prognosis of patients.Methods: Clinical data of 319 patients (case group) who underwent radical resection of CRC in our hospital from June 2015 to March 2018 were collected, simultaneously, 300 people without the apparent physical disease who underwent physical examination in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Another study evaluating a cohort of Chinese patients identified increased ITLN1 levels as a potential risk factor for colorectal cancer (13). Higher levels of circulating ITLN1 were also found to increase the probability of recurrence or death in colorectal cancer after surgery; yet, the difference in circulating ITLN1 between the groups was very small (14). A study by Ummugul Uyeturk and colleagues (15) examined circulating ITLN1 levels after surgery and chemotherapy in colorectal cancer and found that the levels remained elevated compared with a healthy control group who did not have surgery or chemotherapy.…”
Section: Itln1 and Gastrointestinal Cancersmentioning
confidence: 99%
“…Another study evaluating a cohort of Chinese patients identified increased ITLN1 levels as a potential risk factor for colorectal cancer (13). Higher levels of circulating ITLN1 were also found to increase the probability of recurrence or death in colorectal cancer after surgery; yet, the difference in circulating ITLN1 between the groups was very small (14). A study by Ummugul Uyeturk and colleagues (15) examined circulating ITLN1 levels after surgery and chemotherapy in colorectal cancer and found that the levels remained elevated compared with a healthy control group who did not have surgery or chemotherapy.…”
Section: Itln1 and Gastrointestinal Cancersmentioning
confidence: 99%
“…According to a number of studies, plasma ITLN1 is highly expressed in CRC patients and is an independent risk factor for recurrence and survival. 61 In contrast, Katsuya et al 62 found that enhanced tumor expression of ITLN1 was associated with a more favorable prognosis in CRC patients. In this study, MMP1, LGALS4, and ITLN1 were low-risk genes associated with a good prognosis.…”
Section: Discussionmentioning
confidence: 96%
“…Levels of omentin-1, whether low or high, could potentially serve as indicators of cancer progression, with some data suggesting an association between increased omentin levels in blood serum and cancer development [49]. Conversely, other data propose a potential decrease in omentin concentration with the malignancy of cancer [50].…”
Section: Omentinmentioning
confidence: 99%